The effect of cauli flower (Brassica oleracea var. botrytis L.) to the change of : cholesterol, MDA level of rats hiperlipide - Endang Sri Sunarsih; M. Caecilia Nanny S.; Nita Fajaryanti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
The unbalance of oxidant and antioxidant can effect of various diseases, for example atherosclerosis. High total cholesterol level was given the risk factor to atherosclerosis. This research aims to know the effect of cauliflower (Brassica oleracea var. botrytis L.) juice to change of total cholesterol level and peroxide of lipid (MDA level). A twenty white rats Wistar strain were treated as hiperkolesterolemia with consumed a high fat meal for 14 days, then devided in to 4 groups. Group I as positive control was given a green tea leaf infuse through a dosage 0,605 g/ kg BW, group II as negative control was given an aquadestilata. Then Group III and IV as were given cauliflower juice through a dosage 15 mL/ kg BW and 20 mL/ kg BW for 14 days. The result of this research were concluded that cauliflower juice through a dosage 15 mL/ kg BW and 20 mL/ kg BW was decreased of total cholesterol level and lipid peroxide (MDA level). Cauliflower juice through a dosage 20 mL/kg BW was found as an effective dosage to decreased of total cholesterol level and lipid peroxide (MDA level) of male white rats Wistar strain with high fat diet treatment.Key words : Juice, cauliflower, total cholesterol, peroxide of lipid, MDA.